Differential regulation of the phosphorylation of Trimethyl-lysine27 histone H3 at serine 28 in distinct populations of striatal projection neurons. (August 2016) - Bonito-Oliva, Alessandra; Södersten, Erik; Spigolon, Giada; Hu, Xiaochen; Hellysaz, Arash; Falconi, Anastasia; Gomes, Ana-Luisa; Broberger, Christian; Hansen, Klaus; Fisone, Gilberto
Abstract: Phosphorylation of histone H3 (H3) on serine 28 (S28) at genomic regions marked by trimethylation of lysine 27 (H3K27me3) often correlates with increased expression of genes normally repressed by Polycomb group proteins (PcG). We show that amphetamine, an addictive psychostimulant, and haloperidol, a typical antipsychotic drug, increase the phosphorylation of H3 at S28 and that this effect occurs in the context of H3K27me3. The increases in H3K27me3S28p occur in distinct populations of projection neurons located in the striatum, the major component of the basal ganglia. Genetic inactivation of the protein phosphatase-1 inhibitor, dopamine- and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32), reduces the phosphorylation of H3K27me3S28 produced by amphetamine and haloperidol. In contrast, knockout of the mitogen- and stress activated kinase 1 (MSK1), which is implicated in the phosphorylation of histone H3, decreases the effect of amphetamine, but not that of haloperidol. Chromatin immunoprecipitation analysis shows that amphetamine and haloperidol increase the phosphorylation of H3K27me3S28 at the promoter regions of Atf3, Npas4 and Lipg, three genes repressed by PcG. These results identify H3K27me3S28p as a potential mediator of the effects exerted by amphetamine and haloperidol, and suggest that these drugs may act by re-activating PcG repressed target genes. Highlights: We investigated the effect of amphetamine and haloperidol on histone H3 phosphorylation at S28. Both drugs promoted phosphorylation of trimethyl-K27 histone H3 (H3K27me3) at S28. These effects occured in distinct populations of striatal medium spiny neurons (MSNs). Expression of DARPP-32 in these neurons was required for H3K27me3 phosphorylation at S28. The effect of amphetamine was also dependent on the mitogen-and stress-activated kinase-1.